KEKUATAN POLITIK BIROKRASI PADA KEMENANGAN AIRIN RACHMI DIANY DAN BENYAMIN DAVNIE DALAM PEMILUKADA TANGERANG SELATAN 2010-2011 - Raden Iwan Siswadijaya (Universitas Nasional, 2017)
The influence of bureaucratic politics in South Tangerang General Election is very relevant to assess the political situation in the country especially when elections. With kualitati method and the case study approach, then we will see to what extent the bureaucratic politics the role power victory Rachmi Diany Airin and Benjamin Davnie in South Tangerang General Election 2010-2011 Keywords: Politik Birokrasi, PEMILUKADA, Tangerang Selatan